ON SOME PROPERTIES OF LITHUANIAN VERBAL PREFIXES - Korostenskienė, Julija (Verbum, 2015)
In the present article, the methodology developed by Svenonius (2008, 2004a, b) was applied to analyse Lithuanian prefixes as part of the ongoing research on the position of the reflexive/reciprocal marker (i)s(i)- in Lithuanian. Prefixes constitute an interesting domain since they are traditionally believed to induce the movement of the reflexive marker. However, the reasons why the reflexive marker cannot raise beyond a particular point were unclear. Showing first the phrasal status of all verbal prefixes in Lithuanian, the proposed approach divides verbal prefixes into two main groups: lexical and superlexical prefixes. Lexical prefixes derive from prepositions and can contribute both literal and idiosyncratic meanings. They can also change the event structure of the verb as well as affect its argument composition. Meanwhile superlexical prefixes contribute regular temporal or modal meanings and can stack above lexical prefixes. On the basis of these properties, previous research on Germanic particles and Slavic prefixes as well as idiom construction principle outlined in Marantz (1988), the conclusion was made that Lithuanian lexical and superlexical prefixes have different merging positions. Thus lexical prefixes originate within the verbal complex and undergo subsequent movement to an aspectual projection to realise the resultative meaning overtly. Meanwhile superlexical prefixes originate in the respective projections above the projection of lexical prefixes, which is in line with the historical origins of these prefixes. The different merging positions of prefixes help account for the fact why the reflexive/reciprocal marker never raises beyond the lexical prefix: as a physically manifest trace of the subject argument, it stays within the material originating within the verbal complex.